A model for strategic planning for sports marketing for some sub-federations of athletics in Iraq (Global Scientific Review, 2024)
Management in this era has become one of the pillars of progress. There is no discovery, activity, change or achievement except when analyzing its causes, we find that management drives it and stands behind its existence. Any attempt to bring about economic or social development, despite its need for capital, basically needs advanced management that uses scientific methods in planning, organizing, directing and controlling in order to achieve the optimal use of available resources and capabilities.